(untitled) (Fiep Bulletin - online, 2016)
Physical fitness is one of the aspects most required during the formation of the military police, and in their daily police activity in overt and preserve public order. It is therefore vitally important to train these professionals who use technical-scientific and effective methods of physical training. For both study proposed to apply to two groups of 1st year of the Bachelor of Police Sciences Security and Public Order, two different models of periodization, called "BRTAF A" and "B BRTAF". At the end were assessed by a Fitness Test. It was concluded that the two periodization models were effective, however, the model "BRTAF A" tends to be more effective, since it provided a better homogeneity between individuals, and improve more significantly in muscular endurance tests.